Gagasan Yuridis Gratifikasi Seksual Sebagai Bentuk Tindak Pidana Korupsi Di Indonesia - Ayda Rahayu; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Corruption is an enemy of every country in the world, and we all know that money is the mainsource of corruption. Lubis and Scott in their view of corruption say: